2008
DOI: 10.1159/000158665
|View full text |Cite
|
Sign up to set email alerts
|

Promoter Hypermethylation in Tumour Suppressor Genes Shows Association with Stage, Grade and Invasiveness of Bladder Cancer

Abstract: Aims: Superficial bladder cancer is a highly recurrent disease, with progression to muscle invasiveness occurring in 15–30% of cases. Promoter hypermethylation in a panel of tumour suppressor genes involved in cell cycle control, apoptosis and DNA repair was analyzed in superficial bladder tumours in order to evaluate the suitability of epigenetic biomarkers for an earlier prediction of the aggressive course of the disease. Method: Promoter hypermethylation in p16, RARβ, RASSF1A, DAPK, and MGMT genes was analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
42
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(48 citation statements)
references
References 56 publications
5
42
0
1
Order By: Relevance
“…Several groups have reported methylation markers of progression (14,20,23,24,41,42). We identified and validated TBX4 as a promising candidate of disease progression, but in addition to TBX4, we also found markers reported previously.…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…Several groups have reported methylation markers of progression (14,20,23,24,41,42). We identified and validated TBX4 as a promising candidate of disease progression, but in addition to TBX4, we also found markers reported previously.…”
Section: Discussionsupporting
confidence: 54%
“…The POU4F2 protein is a transcription factor encoded by a gene located at chromosome 4q31. 23. POU4F2 has been reported to be a multifunctional protein that interacts with cancer-related genes such as BRCA1 and TP53.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…54,55 UTI-induced CDKN2A methylation could provide a mechanism for the observed correlation between recurrent UTI and bladder carcinoma risk. [56][57][58] After infection, bladder uroepithelial cells undergo apoptosis that results in shedding of infected cells and intracellular pathogens, thereby reducing the overall pathogen load. Cell proliferation of basal cells increases and is followed by cell differentiation to replace lost uroepithelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that methylation status plays an important role in carcinogenesis in various organs, including NMIBC (ref. [21][22][23][24][25][26][27][28][29][30] ). Methylation status is a potent indicator for distinguishing patients responding to BCG from those who are failing to do so and who need the radical therapy approach 31,32 .…”
Section: Discussionmentioning
confidence: 99%